Five-Year Disease-Free Follow-Up of a Borderline Breast Phyllodes Tumor in a 15-year-old Patient - UĞURLU, MUSTAFA ÜMİT (AVES, 2015)
Phyllodes tumors are large breast tumors representing only 1% of breast neoplasms and are rarely seen in young women. Histologically, phyllodes tumors are classified as benign, borderline, or malignant based on the characteristics of the stroma. Although wide local excision is recommended for the treatment modality, the reoccurrence rate after surgical excision varies between 36% and 65%, with recurrence more likely in those with the tumor at the margins of excision. Our aim was to report - a case in a 15-year-old girl with a 115-mm borderline phyllodes tumor in her left breast mimicking a juvenile fibroadenoma. We presented a 5-year disease-free follow-up after wide local excision with negative margins.
Keywords: Phyllodes tumor; recurrence; breast; CARCINOMA; THERAPY